2013
DOI: 10.4103/2156-7514.114809
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Ultrasonographic Parameters with Serum Creatinine in Chronic Kidney Disease

Abstract: Objective:The purpose of our study is to correlate renal echogenicity with serum creatinine in order to determine the significance of renal echogenicity when it comes to identifying the progression of chronic kidney disease (CKD) and for the sonographic grading of CKD.Materials and Methods:Sixty patients above 30 years of age who had been diagnosed with CKD according to the guidelines of the National Kidney Foundation were included in the study. Patients on kidney replacement therapy or with fatty liver findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
42
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 15 publications
12
42
0
6
Order By: Relevance
“…Similar results were obtained by Siddappa et al in a study group of patients over 30 years of age (17) .…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were obtained by Siddappa et al in a study group of patients over 30 years of age (17) .…”
Section: Discussionsupporting
confidence: 90%
“…Change of the parenchymal echogenicity showed the highest sensitivity for low IKGFR/PV, and this is in agreement with the conclusion of a recent human kidney study that found that estimated GFR negatively correlated with parenchymal echogenicity in CKD . Increased renal echogenicity in CKD is histologically related to glomerulosclerosis, tubular atrophy, and interstitial fibrosis, and these histological changes responsible for increased parenchymal echogenicity suggest a permanent decrease of renal function . Despite of this, a change in renal parenchyma echogenicity is not always predictive of irreversible renal lesions, since it is also detected in other renal diseases .…”
Section: Discussionsupporting
confidence: 88%
“…43 Increased renal echogenicity in CKD is histologically related to glomerulosclerosis, tubular atrophy, and interstitial fibrosis, and these histological changes responsible for increased parenchymal echogenicity suggest a permanent decrease of renal function. 44 Despite of this, a change in renal parenchyma echogenicity is not always predictive of irreversible renal lesions, since it is also detected in other renal diseases. 45 Furthermore, in a study of 117 dogs generalized changes in renal parenchymal echogenicity did not correspond to specific histopathological diagnoses of kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…CKD can be diagnosed by its pathological abnormalities, changes in the levels of kidney function markers in the blood or urine, or by imaging investigations. 2 Chronic kidney disease is a significant cause of morbidity and mortality world wide. In India, there is a rising incidence and prevalence of kidney failure, with poor outcomes and high cost.…”
Section: Introductionmentioning
confidence: 99%